Cloning, Expression and Characterization of the α-glucuronidase from the Hyperthermophile DictyoglomusturgidumDSM 6724Ô - Brumm, Phillip; Xie, Dan; Allen, Larry; A. Mead, David (Journal of Enzymes, 2020)
Conversion of biomass into fermentable sugars is a major requirement for successful and cost-effective biofuels production. The conversion of xylan to sugars requires multiple enzymes including α-glucuronidase. Here we report the cloning, expression, purification and characterization of the α-glucuronidase from Dictyoglomusturgidum(DtuAgu). DtuAgu is an intracellular protein of 685 amino acids and a predicted molecular weight of 79.4 kD. Enzymatic activity was optimum between pH 7.0 and 8.0 and at 85°C. The specific activity of the enzyme was 10 u/mg when measured using mixed aldouronic acids. The specific activity on isolated glucuronoxylan was approximately 20% of the value obtained with xylooligosaccharides. DtuAgu significantly improved xylan conversion to xylose when evaluated using two mixtures of thermostable bacterial enzymes and two sources of xylan. DtuAgu has the potential to be a key player in thermostable enzyme cocktails for the conversion to biomass to biofuels.α
Keywords: Dictyoglomus turgidum; alpha-glucuronidase; xylan; glucuronoxylan; β-xylanase; biomass; biofuels